2019
DOI: 10.1038/s41598-019-47300-7
|View full text |Cite
|
Sign up to set email alerts
|

Precise and systematic survey of the efficacy of multicomponent drugs against functional dyspepsia

Abstract: Functional dyspepsia (FD) is one of the most prevalent functional gastrointestinal disorders, and more and more multicomponent drugs represented by traditional Chinese medicines have provided a favorable therapeutic effect in its treatment. However, their precise localization in the clinic, as well as corresponding mechanism, is ambiguous, thus hindering their widespread use. To meet this requirement, a precise and systematic approach based on a restriction of special disease-related molecules and the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…The MS analysis for QE HF was performed with one full scan (300–1,400 m/z, R=120,000 at 400 m/z) at automatic gain control target of 5×105 ions, followed by up to 30 data-dependent MS/MS scans with higher-energy collision dissociation (target 5×105 ions, max injection time 35 ms, normalized collision energy of 32%), detected in the Orbitrap. The dynamic exclusion of previously acquired precursor ions was enabled at 18 s ( Wei et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The MS analysis for QE HF was performed with one full scan (300–1,400 m/z, R=120,000 at 400 m/z) at automatic gain control target of 5×105 ions, followed by up to 30 data-dependent MS/MS scans with higher-energy collision dissociation (target 5×105 ions, max injection time 35 ms, normalized collision energy of 32%), detected in the Orbitrap. The dynamic exclusion of previously acquired precursor ions was enabled at 18 s ( Wei et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, studies have found that Xiangsha Liujunzi Decoction alleviates the symptoms of FD by increasing the production of ghrelin, cholecystokinin and VIP and increasing the levels of these neuropeptides in the circulation[ 89 ]. Moreover, Wei et al[ 90 ] found that XiaoErFuPi granules can increase the levels of motilin, gastrin and gastric emptying rate, and thus have a good effect on patients with FD. Xue et al[ 91 ] isolated and purified magnoloside A (MA) from Magnolia officinalis, and found that MA accelerated the delayed intestinal emptying of FD rats and increased the levels of gastrin, motilin, and calcitonin gene-related proteins, reducing the levels of serotonin, nitric oxide synthase, and VIP.…”
Section: Microbiota-gut-liver-brain Axis and Fdmentioning
confidence: 99%
“…Default settings were used for variable and fixed modifications (variable modification: acetylation (protein-N terminus) and oxidation methionine (M)), fixed modification: carbamidomethylation (C). A MaxQuant label-free quantification (LFQ) algorithm was used to quantitate the MS signals, and the intensities of proteins were represented in intensity based absolute protein quantification (iBAQ) (Wei et al, 2019b). The iBAQ of each sample was transferred into a fraction of total protein iBAQ amount per experiment (FOT).…”
Section: Lc-esi-ms/ms Measurements and Protein Quantificationmentioning
confidence: 99%